2016
DOI: 10.1038/nm.4125
|View full text |Cite
|
Sign up to set email alerts
|

Distinct evolution and dynamics of epigenetic and genetic heterogeneity in acute myeloid leukemia

Abstract: Genetic heterogeneity contributes to clinical outcome and progression of most tumors. Yet, little is known regarding allelic diversity for epigenetic compartments and almost no data exists for acute myeloid leukemia (AML). Here we examined epigenetic heterogeneity as assessed by cytosine methylation within defined genomic loci with four CpGs (epigenetic alleles), somatic mutations and transcriptomes of AML patient samples at serial time points. We observe that epigenetic allele burden is linked to inferior out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
334
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(351 citation statements)
references
References 77 publications
9
334
2
Order By: Relevance
“…Recently it was shown that the constitution of AML at relapse may differ from diagnosis due to clonal changes including clonal evolution, clonal regression and clonal selection, with possible changes on immunophenotypic [32,33], cytogenetic [34], genetic [34,35] and epigenetic [35] level. Detailed whole genome sequencing studies, analyzing paired diagnosis-relapse samples, showed that at time of diagnosis, patients could present with a wide array of small subclones of which some remained in relapse [36]: indicative for clonal selection under therapy pressure.…”
Section: Lsc Heterogeneity Of Lsc Within a Patientmentioning
confidence: 99%
“…Recently it was shown that the constitution of AML at relapse may differ from diagnosis due to clonal changes including clonal evolution, clonal regression and clonal selection, with possible changes on immunophenotypic [32,33], cytogenetic [34], genetic [34,35] and epigenetic [35] level. Detailed whole genome sequencing studies, analyzing paired diagnosis-relapse samples, showed that at time of diagnosis, patients could present with a wide array of small subclones of which some remained in relapse [36]: indicative for clonal selection under therapy pressure.…”
Section: Lsc Heterogeneity Of Lsc Within a Patientmentioning
confidence: 99%
“…Epi-alleles also contain information relevant to clinical prognosis that are independent of mutation status. 53 Although what drives the underlying epigenetic heterogeneity is unclear, it appears to be contributory to the molecular heterogeneity in AML and should be explored in CMML.…”
Section: Epigenomic Phenotypesmentioning
confidence: 99%
“…Whole exome sequencing and whole genome sequencing Whole exome sequencing on EMC-AML-1 was performed as previously described 3 . For WEHI-AML-1 and WEHI-AML-2, DNA was extracted using either the MagAttract DNA Blood M48 Kit or QIAsymphony DSP DNA Mini Kit (Qiagen, Venlo, the Netherlands).…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…Aligned sequencing data (BAM files aligned to hg38) was downloaded from GDC, together with variant calls. Preliminary variant detection of WEHI-AML-1, WEHI-AML-2, EMC-AML-1, the EMC cohort [phs001027] 3 and all TCGA-AML [phs000178] 6 samples was performed with samtools version 0.1.19-44428cd, followed by Varscan v2.3.6 7 . These preliminary calls were refined with superFreq 0.9.15 with default settings, which also provided clonality estimates for copy number and somatic SNV calls 8 .…”
Section: Rna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation